2022
DOI: 10.1111/zph.12941
|View full text |Cite
|
Sign up to set email alerts
|

Tick‐borne encephalitis virus and West‐Nile fever virus as causes of serous meningitis of unknown origin in Kazakhstan

Abstract: Flaviviruses are a family of viruses that cause many diseases in humans. Their similarity in the antigenic structure causes a cross‐reaction, which complicates the precise diagnostic of disease causing agents. Tick‐borne encephalitis virus (TBEV), a member of the flavivirus family, is the cause of tick‐borne encephalitis (TBE). Worldwide the awareness of this disease is raising, however, in many countries such as the Republic of Kazakhstan (KZ) there is a lack of serological investigation of flaviviruses in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
1
0
1
Order By: Relevance
“…Іноді хворі можуть скаржитись на біль у животі. На цьому етапі при проведенні серологічного дослідження змін у лікворі не виявляють [9]. Початок другої фази проявляється приблизно у 50 % випадків як ізольований менінгіт, приблизно в 40 % -як запалення оболонок мозку (менінгоенцефаліт) і приблизно у 10 % -як запалення оболонок спинного мозку (менінгоенцефаломієліт) (Kaiser, 1999).…”
Section: результати та обговоренняunclassified
“…Іноді хворі можуть скаржитись на біль у животі. На цьому етапі при проведенні серологічного дослідження змін у лікворі не виявляють [9]. Початок другої фази проявляється приблизно у 50 % випадків як ізольований менінгіт, приблизно в 40 % -як запалення оболонок мозку (менінгоенцефаліт) і приблизно у 10 % -як запалення оболонок спинного мозку (менінгоенцефаломієліт) (Kaiser, 1999).…”
Section: результати та обговоренняunclassified
“…Between 2016 and 2020, approximately 3000 cases were registered in EU/EEA (European Union and European Economic Area) countries annually [ 18 ] and 1500–2000 cases were recorded in Russia over the last six years (2013–2018) [ 19 ]. In Kazakhstan, about 363 cases of TBE were reported in the last ten years (2011–2020) [ 20 ]. Tick-borne diseases are also suspected to be endemic in other countries in Central Asia, including Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan [ 21 ], but few studies have been conducted in these areas, except for one study where TBEV was found in Kyrgyzstan ticks [ 22 ].…”
Section: Introductionmentioning
confidence: 99%